AN INVESTIGATION THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND EXTERNAL CUSTOMER SATISFACTION ORIENTATION (An Empirical Study of four stars hotels in Tripoli- Libya) - Zaroug, Yousef Ali Mohamed; Thoyib, Armanu; Hadiwidjojo, Djumilah; Solaimun, Ir (Accounting Department,, 2020)
ABSTRACT Purpose — This research was conducted to study the effect of information sharing and information quality toward supply chain integration and farmer business performance.Design/methodology/approach — The type of this research is quantitative explanatory research. The data used in this study are primary data obtained by questionnaire. The sampling method uses multistage proportional random sampling, sample obtained amount 200 farmers. Data analysis in this study uses path analysis method with SPSS 23.Findings — The results of this research indicate that the quality of information is not significant to the integration of supply chain and farmer business performance. Information sharing has a positive and significant effect toward supply chain integration and farmer business performance, supply chain integration has a positive and significant effect toward farmer business performance.Practical Implications — Increasing global business competition and efforts to shorten product life cycles are the two main factors that encourage businesses to change their focus from competitive competition to mutually beneficial relationships and cooperation to improve business performance.Originality/value — The main objective of supply chain activities for business activities is a crucial element because with these activities the goods produced can reach the end consumers.Keywords — Information Sharing, Information Quality, Supply Chain Integration, Enterprise Performance.